The Impact of Sustainability Reporting as a Moderating Effect on the Relationship Between Tax Avoidance and Firm Value - Tifanny Jubilim; Widijaya Widijaya (Jurnal Akuntansi dan Keuangan, 2023)
This study aims to examine the moderating impact of sustainability reports on the relationship between tax avoidance with firm value. Tax avoidance is measured by using two indicators: effective tax rate (ETR) and GAAP effective tax rate (GAAP ETR), while sustainability reports are assessed based on the Global Reporting Initiative (GRI) standards. The sample for this study consists of companies listed on the Indonesia Stock Exchange (IDX) that have published sustainability report in the 2017-2021 period. Purposive sampling was used in this study to select data, resulting in a final sample of 57 companies that meet the established criteria. This research shows that there is no significant effect between tax avoidance and firm value that moderated by sustainability reports.